Non-Pharmacological Therapies in the Management of Tension-Type Headache – A Literature Review - Katra, Małgorzata; Szczęsny , Mikołaj; Pal , Adrian; Cienkowski , Krzysztof; Cegiełka , Patryk; Ślot , Marcin; Żeżawska , Karolina; Głowacka , Izabella; Adamczyk, Aleksandra; Sicińska, Maria (Journal of Education, Health and Sport, 2026)
Background Tension-type headache (TTH) is, alongside migraine, the most common primary headache disorder worldwide and a leading cause of years lived with disability. Although often mild and self-limiting, many patients develop frequent or chronic TTH, which is associated with reduced quality of life, decreased productivity, and increased use of analgesics, raising the risk of medication-overuse headache. These issues highlight the need for effective non-pharmacological management strategies. Aim To summarize evidence published between 2015 and 2025 on the effectiveness of non-pharmacological interventions in TTH management. Methods A structured search of PubMed and Google Scholar identified studies, including randomized controlled trials, systematic reviews, meta-analyses, and cohort studies evaluating non-pharmacological interventions in adults with episodic or chronic TTH. Due to heterogeneity in study design and outcomes, a qualitative narrative synthesis was conducted. Results The strongest evidence supports multimodal physiotherapy approaches, including manual therapy, strengthening and stretching exercises, and aerobic training, which reduce pain intensity and headache frequency. Psychological interventions—especially cognitive behavioral therapy, relaxation techniques, biofeedback, and mindfulness-based approaches—show moderate to strong effectiveness in reducing headache frequency, pain intensity, and stress-related symptoms. Emerging evidence suggests that dietary supplementation may provide modest additional benefits. Overall, non-pharmacological approaches appear most effective when delivered within a multidisciplinary framework. Conclusions Non-pharmacological interventions are an evidence-based component of TTH management. Physiotherapy and psychological therapies show the most consistent benefits, while supplementation may serve as an adjunct in selected patients. Further high-quality randomized trials with standardized outcomes are needed.